Proposta de equipamento de coleta de pinos e alarmes no varejo de moda por meio do IoT - Oliveira, Douglas Eldo Pereira de (2023)
The clothing market is one of the largest national economic markets, and it has been growing rapidly in recent years. Brazil's clothing sector generated R$ 134 million in e-commerce revenue, with 1.57 billion accesses between March 2021 and March 2022. Given these figures, it is imperative to improve production processes, including logistics within operations. This study discovered that there are no studies on the financial viability of product and input collection systems based on RFID and IoT. To fill this gap, the objective was to propose IoT-based collection equipment that optimizes resources for collecting pins and alarms in fashion retail stores. The systematic literature review method was used as the foundation for the theoretical-conceptual proposal of IoT-based equipment for collecting pins and alarms. Additionally, the proposed equipment was applied in a case study at a fashion retailer. The experiment demonstrated that the new proposed process optimizes and improves the operation. Investments to acquire the entire retail network proved appealing, paying for themselves in the worst-case scenario in 5 years.